Acute Kidney Injury Following Snake Bite in a Child with Congenital Renal Anomaly - Sudhan Ekam baram; Amish Undani; Vijaya kumar Mahaleengam; Prahlad Nageswaran; Shweta Priyadarshini; Edwin Fernando (Asian Journal of Clinical Pediatrics and Neonatology, 2018)
A 7 year old boy presented with acute kidney injury (AKI) following snake bite despite anti - snake venom (ASV) administration. This was secondary to disseminated intravascular coagulation (DIC) and rhabdomyolysis. He improved with hemodialysis and supportive management. At discharge he had normal renal functions and urine output. The clinical course was suggestive of acute tubular necrosis. The pathogenesis and therapy of snake bite is discussed. This is the first case report of AKI following snake bite in a child with congenital renal anomaly.